A Subtle Subversion: From Arabo-Centrism to Universalism in the 5th/11th Century Šāfiʿī School’s Considerations of Lineage for Marriage Suitability (Kafāʾa) - Soufi, Youcef L. (Arabica, 2024)
The Arab socio-political dominance of 7th-8th century AD Muslim conquerors made its way into the classical legal discourse on kafāʾa (suitable matches in marriage). Most classical jurists considered the marriage of an Arab woman to a non-Arab man to be one of several potential sources of shame to the bride and her family. This article traces how the Persian scholars of the Šāfiʿī school in Khurasan subverted Arabo-centrism in considerations of marriage by reinterpreting the legal doctrine of kafāʾa in the late 10th-11th centuries. Khurasanian Šāfiʿīs built upon but ultimately departed from the position of their colleagues in Iraq on Arab superiority: They formulated a new understanding of lineage which excluded considerations of ethnicity. The discussion of the doctrine of kafāʾa provides an example of how non-Arabs carved a place for themselves within an Islamic legal culture that originally disadvantaged them.